A Study on Calculation of Optimum Exchanged Grinding Wheel Diameter When Surface Grinding Stainless Steel - Nguyen, Quoc Tuan; Le, Xuan Hung; Lien, Vu Thi; Pi, Vu Ngoc; Ky, Le Hong; Hong, Tran Thi; Tung, Luu Anh; Hoang, Tien Dung (Materials science forum, 2020)
This study aims to propose a method to calculate optimum exchanged grinding wheel diameter to minimize grinding cost in grinding surface process for stainless steel. The interactions of the grinding cost and optimum exchanged grinding wheel diameter have been analyzed and presented in mathematical formulae. To obtain the minimal grinding cost, the optimal exchanged grinding wheel diameter has been determined by investigating six two-level grinding process parameters including initial grinding wheel diameter, total dressing depth, radial grinding wheel wear per dress, wheel life, machine tool hour and grinding wheel cost. Based on 26 experiments conducted in computational program, the optimal exchanged grinding wheel diameter is presented as a function of these grinding parameters. This developed model has been verified and proven by experimental results. The proposed method of calculation of the optimum exchanged grinding wheel diameter can be applied in practice to reduce the grinding cost.